VERTICAL EXISTENCE OF COPROSTANOL IN A SEDIMENT CORE FROM SEMARANG COASTAL WATERS, CENTRAL JAVA, INDONESIA - Tonny Bachtiar (JOURNAL OF COASTAL DEVELOPMENT, 2004)
Coprostanol has been proposed as an indicator of domestic (sewage) pollution by researchers because constraint of using coliform bacteria as the indicators of domestic pollution in the environment with high environmental stress, such as urban coastal waters. Increasing the volume of industrial wastes, toxic and heated, the changing of water salinity from low (freshwater) to high (sea water), and decreasing of dissolved oxygen (DO) in the waters, are the constrain factors of bacteria growth. How ever, all the researches have been done in the temperate (high latitude) regions. Information existence of coprostanol in tropical region, especially in Indonesia is still very poor. To understand the existence of coprostanol in the sediments, one core sediment sample (60 cm) was collected from Semarang coastal water adjacent to Banjir Kanal Timur which is the main drainage system of the East Semarang municipal district in Central Java by using a small gravity corer in July 2001. The core sediment sample was divided into 12 sections (5 cm each) for analyzing the concentration of coprostanol, grain size, and TOC. The result shows that coprostanol could be detected in all sample sections (vary from 1.06 to 2.94 mg/g). Coprostanol has significant positive correlation with TOC, but not significant with grain size. Coprostanol has very significant negative correlation with the depth of core. Based on the potency of sedimentation rate analysis on Banjir Kanal Timur Semarang coastal waters (0.35 cm/month), the 60 cm core sediment was predicted as a result of 14 –16 year sedimentation. All of these facts show that coprostanol has an excellent persistence in the sediment of tropical environment, and reflect that coprostanol has a potency as an alternative indicator of domestic waste pollution in urban tropical coastal waters. ageG'p x environments by Indonesian scientists. This is mainly because of the lack of knowledge in the field of deep-sea microbiology in Indonesia.